Peran Digital Marketing pada UMKM dengan Prinsip-prinsip Syariah - Awa, Awa; Safari, Apay; Riyanti, Anti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2024)
The rapid development of technology has greatly changed the marketing landscape in the world, where marketing methods that were previously completely traditional and conventional have now been integrated into the digital world. Understanding and awareness of the importance, role and influence of digital marketing in micro, small and medium enterprises (MSMEs) is still low. Its implementation is still considered not that important, on the grounds that the business being run is not a large business that requires digital marketing. Including its implementation of sharia principles is still very minimal. Research that explores the role of digital marketing in MSMEs with sharia principles in a comprehensive manner has never been conducted before. The aim of the research is to explore the role of digital marketing in MSMEs with sharia principles. The method used is library research, using critical analysis techniques. The results of research regarding the role or impact or influence of digital marketing in MSMEs with sharia principles are on the following 15 things: (1) facilitate access to information; (2) marketing products; (3) become a superior product; (4) healthy competition; (5) expanding target/market share; (6) expanding geographic reach; (7) building trust and reputation; (8) purchasing decisions; (9) increase in income; (10) increase in sales; (11) increasing business performance; (12) business sustainability and success; (13) application of Islamic marketing ethics; (14) development of halal label MSMEs; and (15) development of MSMEs through cooperatives.